2006
DOI: 10.1590/s1415-52732006000200004
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da multimistura no estado nutricional de pré-escolares matriculados em creches

Abstract: ObjetivoAvaliar o impacto da suplementação da dieta com multimistura sobre o estado nutricional de crianças em fase pré-escolar em risco nutricional. MétodosTrata-se de estudo tipo duplo cego com duração de dois meses e acompanhamento longitudinal de 135 crianças na faixa etária de um a seis anos. As crianças foram divididas em três grupos: intervenção 1 (GI1 n=48), intervenção 2 (GI2 n=45) e controle (GC n=42), recebendo 5g e 10g de multimistura e placebo, respectivamente. O estado nutricional das crianças em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
2
0
6
Order By: Relevance
“…In the analysis does not take account of grouping, results will be artificially elevated and confidence intervals will be narrower, increasing the chance of spuriously significant findings and erroneous conclusions, as may have occurred in the studies cited above. 6,7 Multilevel models that take account of the hierarchical nature of the data are appropriate for analysis of studies randomized by groups. 13 The lack of impact of supplementing with multimixture the diet of children who attend municipal preschools may, in part, be explained by the fact that both the children at the intervention schools and those in the control group were already receiving adequate meals for their age group daily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis does not take account of grouping, results will be artificially elevated and confidence intervals will be narrower, increasing the chance of spuriously significant findings and erroneous conclusions, as may have occurred in the studies cited above. 6,7 Multilevel models that take account of the hierarchical nature of the data are appropriate for analysis of studies randomized by groups. 13 The lack of impact of supplementing with multimixture the diet of children who attend municipal preschools may, in part, be explained by the fact that both the children at the intervention schools and those in the control group were already receiving adequate meals for their age group daily.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although the multimixture is widely used nationwide, and is also the subject of criticism from professional associations, 4,5 few controlled studies could be identified in the literature that had evaluated the impact of the multimixture. 6,7 It should also be pointed out that the studies that were found were not randomized and suffer methodological limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, desde 1985 a multimistura vem sendo difundida pela Pastoral da Criança e ganhando evidência entre as ações de combate à desnutrição infantil. A multimistura, que faz parte da proposta de alimentação alternativa, é preparada a partir de ingredientes de baixo custo e fácil acesso, geralmente farinhas e farelos de cereais, sementes, pós de folhas verdes e de casca de ovos (OLIVEIRA et al, 2006). Os principais argumentos apresentados pelos defensores de sua adoção como medida de prevenção e tratamento da desnutrição são a disponibilidade de seus ingredientes, a não interferência nos hábitos alimentares da população, o baixo custo, a possibilidade de produção caseira e a acessibilidade de praticamente toda a população, em especial a de baixa renda (FERREIRA et al, 2005).…”
Section: Introductionunclassified
“…A realização de ensaios biológicos, utilizando ratos como modelo experimental (BOAVENTURA et al, 2000;MADRUGA et al, 2004), e estudos com crianças em risco nutricional (OLIVEIRA et al, 2006) não indicaram a multimistura como um suplemento adequado, na recuperação ou na manutenção do estado nutricional. No entanto, estes ensaios têm avaliado a multimistura como alternativa isolada de combate à desnutrição, não considerando a realidade da dieta das populações assistidas e as diferentes formulações de multimisturas que têm sido difundidas.…”
Section: Introductionunclassified
“…Apesar do uso da multimistura estar disseminado em todo o país e, ao mesmo tempo, ser alvo de críticas por entidades profissionais 4,5 , poucos estudos controlados de avaliação do impacto da multimistura foram identificados na revisão da literatura 6,7 . Cabe destacar que esses estudos não foram randomizados e apresentam limitações metodológicas.…”
Section: Introductionunclassified